2007
DOI: 10.1021/jf0630217
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Olive Oil Polyphenols against Helicobacter pylori

Abstract: Helicobacter pylori is linked to a majority of peptic ulcers and to some types of gastric cancer, and resistance of the microorganism to antibiotic treatment is now found worldwide. Virgin olive oil is an unrefined vegetable oil that contains a significant amount of phenolic compounds. Under simulated conditions, we have demonstrated that these substances can diffuse from the oil into the gastric juice and be stable for hours in this acidic environment. In vitro, they exerted a strong bactericidal activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 42 publications
1
102
1
5
Order By: Relevance
“…Oleuropein (Bisignano et al, 1999;Furneri et al, 2004), hydroxytyrosol (Bisignano et al, 1999) which inhibits or delays the growth rate of a range of bacteria. Romero et al (2007) reported that the dialdehydic form of decarboxymethyl oleuropein aglycon and the dialdehydic form of decarboxymethyl ligstroside aids in inhibit ing the growth of Helicobacter pylori. Recently, Bubonja-Songe et al (2011) indicated that olive oil polyphenols can be used as an alternative for the prevention of food spoilage and monocytogenes contaminated with Listeria.…”
Section: Introductionmentioning
confidence: 99%
“…Oleuropein (Bisignano et al, 1999;Furneri et al, 2004), hydroxytyrosol (Bisignano et al, 1999) which inhibits or delays the growth rate of a range of bacteria. Romero et al (2007) reported that the dialdehydic form of decarboxymethyl oleuropein aglycon and the dialdehydic form of decarboxymethyl ligstroside aids in inhibit ing the growth of Helicobacter pylori. Recently, Bubonja-Songe et al (2011) indicated that olive oil polyphenols can be used as an alternative for the prevention of food spoilage and monocytogenes contaminated with Listeria.…”
Section: Introductionmentioning
confidence: 99%
“…Shikov et al (2008) reported that some oil extracts, like Chamomilla recutita oil extract, have antibacterial activity. In their study, Romero et al, (2007) investigated the antibacterial effect of olive oil on 3 different types of H. pylori strains and showed that olive oil extracts, rich in phenolic compounds, had antibacterial effects on H.pylori. Kubo and his colleagues (1995) observed antimicrobial activity of olive oil flavour compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds of virgin olive oil presented a strong bactericidal effect against eight strains of Helicobacter pylori, which is responsible for ulcers and some types of gastric cancer; among the strains tested three were resistant to antibiotics [108]. The secoiridoid aglycones, in particular decarboxymethyl ligstroside aglycone, were the most effective phenolic components against H. pylori.…”
Section: Antimicrobial Agents Olive Oilmentioning
confidence: 96%
“…This latter compound is effective against mycoplasmal infections at low concentrations [113] and, hydroxytyrosol is absorbed by the human body after virgin oil consumption, as indicated by its presence in urine and plasma samples [114]. Tyrosol is generally less active as antimicrobial agent than the previously mentioned phenolic compounds, it showed nearly no effect on H. pylori [108] and concentrations higher than 100 mM were needed to inhibit Lactobacillus plantarum growth [115].…”
Section: Antimicrobial Agents Olive Oilmentioning
confidence: 99%